Characteristics of Law and Legal Research Methods - Ansori Maulana; Yasmirah Mandasari Saragih; Tamaulina Br Sembiring; Amos Harita; Andi Gultom (Green Social: International Journal of Law and Civil Affairs, 2025)
Law has a regulatory and coercive nature, which means that everyone must obey the existing orders and prohibitions to maintain order and justice in society. The main purpose of law is to create order and justice. The legal research method is a way used to study legal rules and their application. This research is usually conducted with a scientific approach, namely looking for relevant data to answer existing problems. One method used is qualitative research, where researchers examine existing legal literature or sources to understand legal concepts more deeply. In legal research, there are two main approaches: first, studying the legal texts themselves normative studies, and second, seeing how the law is applied in society empirical approaches. These two approaches help us understand the law from a theoretical and practical perspective.